Revisiting the relationship of CSR and corporate philanthropy by using alignment theory - Georg von Schnurbein; Sara Stühlinger (University of Basel, Center for Philanthropy Studies (CEPS), 2015)
Both, CSR and corporate philanthropy are expressions of the interferences between the company and its societal environment. However, the question of the relationship between CSR and corporate philanthropy remains unclear. We apply alignment theory to shed light on the interdependencies of CSR and corporate philanthropy. The relationship may be based on alignment, misalignment, or non-alignment. Our research is based on an empiric analysis of the sustainability rating of U.S. companies and its influence on the related corporate foundation expenditures. Our main finding is that there is no clear relationship between sustainability rating and the annual expenditures of the corporate foundation. Hence, we call for further studies on the exclusive role of corporate philanthropy. While corporate social responsibility is closely related to the core business, corporate philanthropy is voluntary by nature. – – Sowohl Corporate Social Responsibility (CSR) als auch Corporate Philanthropy sind ein Ausdruck des Verhältnisses eines Unternehmens und dem gesellschaftlichen Umfeld. Jedoch bleibt die Beziehung zwischen beiden Konzepten unklar. Mit Hilfe der Alignment Theorie untersuchen wir deren Zusammenhänge. Gemäss dieser Theorie lassen sich die drei Konfigurationen Ausrichtung, Fehlausrichtung und Nicht-Ausrichtung unterscheiden. Die Untersuchung beruht auf einer empirischen Analyse der Nachhaltigkeitsratings amerikanischer Unternehmen und der Ausschüttungen ihrer jeweiligen Firmenstiftungen. Als Hauptergebnis zeigen wir auf, das CSR kaum Einfluss auf Corporate Philanthropy hat, was für eine Nicht-Ausrichtung spricht. Dieser Befund erfordert weitere Untersuchungen zur spezifischen Rolle der Corporate Philanthropy. Während CSR nah am Kerngeschäft des Unternehmens ausgerichtet ist, beruht Corporate Philanthropy auf Freiwilligkeit.
Keywords: A13; L 31; M14; 330; Corporate Foundations; Alignment Theory; Corporate Social Responsibility; Corporate Philanthropy; Sustainability; Firmenstiftungen; Nachhaltigkeit